2019
DOI: 10.1007/s00167-019-05661-6
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation autologous chondrocyte implantation after failed bone marrow stimulation leads to inferior clinical results

Abstract: Purpose Third-generation autologous chondrocyte implantation (ACI) is an established and frequently used method and successful method for the treatment of full-thickness cartilage defects in the knee. There are also an increasing number of patients with autologous chondrocyte implantation as a second-line therapy that is used after failed bone marrow stimulation in the patient's history. The purpose of this study is to investigate the effect of previous bone marrow stimulation on subsequent autologous chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Interestingly, many clinical biomaterials for AC repair consist of collagen type I and/or type III, (e.g., as a fleece [ 228 , 229 ], sponge [ 230 , 231 , 232 , 233 , 234 ], gel [ 235 ], membrane [ 236 , 237 ], or matrix [ 235 , 238 ]) that in some cases are substituted with other materials. hCH culture on collagen type I or II promotes matrix production and turnover without significant differences between collagen types I and II, indicating that the use of collagen type I or II coating for in vitro models appears to be a sound basis for in vivo repair procedures [ 239 ].…”
Section: Collagen Type II Fragment Production and Subsequent Catamentioning
confidence: 99%
“…Interestingly, many clinical biomaterials for AC repair consist of collagen type I and/or type III, (e.g., as a fleece [ 228 , 229 ], sponge [ 230 , 231 , 232 , 233 , 234 ], gel [ 235 ], membrane [ 236 , 237 ], or matrix [ 235 , 238 ]) that in some cases are substituted with other materials. hCH culture on collagen type I or II promotes matrix production and turnover without significant differences between collagen types I and II, indicating that the use of collagen type I or II coating for in vitro models appears to be a sound basis for in vivo repair procedures [ 239 ].…”
Section: Collagen Type II Fragment Production and Subsequent Catamentioning
confidence: 99%
“…59 In a study comparing primary Novocart 3D to Novocart 3D for revision after failed MST in large cartilage defects (mean 5.4 cm 2 ), Müller et al demonstrated significantly improved clinical outcome scores in both groups, although with significantly better outcomes in the primary group. 60 There were no revision surgeries in the primary Novocart 3D group, while the revision group had a 30% reoperation rate.…”
Section: Third-generation Autologous Chondrocyte Implant: Novocart 3dmentioning
confidence: 84%
“… NOVOCART® 3D ( Table 1 ) is a type I/III collagen biphasic scaffold. The trial by Müller et al [ 59 ] confirmed that the IKDC score and visual analog scale (VAS) score at 6, 12, 24, and 36 months after NOVOCART® 3D implantation were significantly better than those preoperation. In addition, compared with the patients who received NOVOCART® 3D treatment after the failure of bone marrow stimulation, those who received NOVOCART® 3D as the first choice had significantly better postoperative IKDC and VAS results, and the operation failure rate was lower.…”
Section: Current Strategies For Articular Cartilage Regenerationmentioning
confidence: 99%